Extraction and thermal dissolution of Piliqing subbituminous coal. (15th July 2017) - Wang, Ya-Nan; Wei, Xian-Yong; Li, Zhan-Ku; Yan, Hong-Lei; Wang, Tie-Min; Zhang, Yang-Yang; Zong, Zhi-Min; Ma, Feng-Yun; Liu, Jing-Mei
Highlights: Totally, 36% of organic matter in PSBC was released by the extraction and TD. EP is rich in NAs and arenes, while DAAs are abundant in SP1 and esters in SP2 –SP4 . A mechanism for the formation of esters was proposed. The oxygen content and aromatic cluster size of R4 are less than those of PSBC and RE . Abstract: Piliqing subbituminous coal (PSBC) was exhaustively extracted with isometric acetone/carbon disulfide mixed solvent under ultrasonic irradiation to afford extractable portion (EP) and extraction residue (RE ). Then RE was subjected to sequential thermal dissolution (TD) in ethanol at 200, 240, 280, and 320 °C and TD at each temperature was conducted for 2 h. The sequential TD provided soluble portions (SPs) 1–4 (SP1 –SP4 ) and residue 4 (R4 ). EP and the SPs were analyzed with a gas chromatograph/mass spectrometer and Fourier transform infrared (FTIR) spectrometer, while PSBC, RE, and R4 were characterized with a solid-state 13 C nuclear magnetic resonance (SS 13 C NMR), FTIR, and X-ray photoelectron spectrometer (XPS). In total, ca. 36 wt% of organic matter was released from PSBC by the ultrasonic extraction and sequential TD. EP is rich in normal alkanes and arenes, while dialkoxyalkanes are predominant in SP1 and esters are the main compounds in SP2 –SP4 . No significant difference in the distribution of functional groups was observed in FTIR spectra of PSBC and RE, while the distribution of functional groups in R4 is significantly different from that in either PSBC or RE . According to analysis with XPS, the content of oxygen-containing species in R4 is relatively low. PSBC consists of 32.6% aliphatic carbon atoms, 63.0% aromatic carbon atoms, and 4.4% carbonyl carbon atoms, while the content (2.0%) of carbonyl carbon atoms in R4 is significantly lower than that (4.4%) in PSBC based on analysis with SS 13 C NMR.